2014
DOI: 10.1371/journal.pone.0096562
|View full text |Cite
|
Sign up to set email alerts
|

Significant Productivity Improvement of the Baculovirus Expression Vector System by Engineering a Novel Expression Cassette

Abstract: Here we describe the development of a baculovirus vector expression cassette containing rearranged baculovirus-derived genetic regulatory elements. This newly designed expression cassette conferred significant production improvements to the baculovirus expression vector system (BEVS), including prolonged cell integrity after infection, improved protein integrity, and around 4-fold increase in recombinant protein production yields in insect cells with respect to a standard baculovirus vector. The expression cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 57 publications
2
34
0
Order By: Relevance
“…The efficacy of the polyhedrin and p10 promoters has been reported to be similar . In the current study, we expressed the polyhedrin under the control of the p10 promoter and found that OBs could be formed regularly.…”
Section: Discussionsupporting
confidence: 85%
“…The efficacy of the polyhedrin and p10 promoters has been reported to be similar . In the current study, we expressed the polyhedrin under the control of the p10 promoter and found that OBs could be formed regularly.…”
Section: Discussionsupporting
confidence: 85%
“…17,18 G omez-Sebasti an et al engineered a novel expression cassette containing various baculovirus genomic elements such as transactivators IE1 and IE0 and enhancer sequences. 18 Insect cells infected with those viruses showed increased cell viability and integrity after infection, and an increase in recombinant protein yields. A similar effect was achieved when the baculovirus apoptotic inhibitor P35 was constitutively expressed from the insect cells.…”
Section: Introductionmentioning
confidence: 99%
“…The problem with these systems, however, is that it is difficult to produce some glycoproteins in sufficient quantities. In most of the previous studies, therefore, focused on the improvement of host glycosylation pathway and baculovirus vector to increase protein production in both quantity and quality [2][3][4].…”
Section: Introductionmentioning
confidence: 99%